STRATEGY FOR IMPLEMENTING GREEN HUMAN RESOURCE MANAGEMENT IN MICRO SMALL MEDIUM ENTERPRISES - Lyra Lasita; Dessy Amanda; Sultan Hibrizi; Wira Kurniawan Panjaitan; Fahrul Rozi Tarigan; Abdul Hafiz (Universitas Efarina, 2024)
This article discusses the strategy for implementing Green Human Resource Management (GHRM) in Micro, Small, and Medium Enterprises (MSMEs) in Indonesia. This research highlights the significant potential for the development of green technology in MSMEs, as well as the role of human resources in achieving sustainable development. GHRMs are considered important in promoting environmentally friendly practices within the organization, which can improve the organization's performance and employees' commitment to green initiatives. Some of the key points discussed included the growth of MSMEs in Indonesia and their contribution to the economy and job creation, the challenges faced by MSMEs related to funding and resources, and the need to adopt GHRM practices such as recruitment, training, and environmentally friendly performance management. GHRM's objectives include promoting the sustainable use of resources and improving the environmental performance of the organization. This study also raises several research questions regarding MSMEs' knowledge about GHRM, the development of GHRM in Indonesia, and its implementation strategies.